Analysis of the economic impact of a disaggregated agricultural sector in South Africa : a Social Accounting Matrix (SAM) multiplier approach - Phoofolo, Makhetha Lambert (Stellenbosch : Stellenbosch University, 2018)
Thesis (MCom)--Stellenbosch University, 2018.